Ocean pressure data measured beneath the Ross Ice Shelf responding to the 2022 Hunga Tonga–Hunga Haʻapai tsunami - Stewart, Craig; Horgan, Huw; Stevens, Craig; SOOS, Southern Ocean Observing System (SEANOE, 2022)
On the 15 January 2022, the volcano Hunga Tonga–Hunga Ha'apai in the southwest Pacific Ocean (20°32'32.37"S 175°23'38.67"W) erupted in what proved to be the most powerful such event since Krakatau in 1883. Among the many impacts of the eruption, a substantial tsunami propagated throughout the southwest Pacific Ocean. The signatures of the eruption were recorded at a wide range of recording stations globally including the atmospheric pressure wave, the tsunami itself and in addition, higher order responses such as a tsunami associated with the pressure wave. Here we describe what is likely the most southerly oceanic measurement of the tsunami arrival as the event was detected in a sub-ice mooring at the grounding line of the Ross Ice Shelf at 82.47 o South. It was recorded on the margin of the Ross Ice Shelf along the Siple Coast at the KIS2 (Kamb Ice Stream 2) field camp by instruments deployed to record ice-ocean interactions in order to improve understand ocean effects on ice sheet stability. The data were recorded at the Kamb Ice Stream KIS2 camp (Latitude -82.470442; Longitude -152.291643°). The channel is around 6 km long, 250 m high and 150 m wide beneath 410 m of ice and snow. In early 2022 a hot water borehole was drilled through the ice shelf to access the ocean. Hydrographic instruments were suspended in the ocean cavity late on the 11th of January 2022 local time and four days later and 7,000 km to the north, the Hunga Tonga–Hunga Ha'apai eruption occurred. At the instrument location the ice underside was at a pressure of 409 dbar and the sea floor was at 650 dbar. The instruments providing the data were three RBR Concerto CTDs (conductivity temperature depth instruments). These instruments included a pressure sensor rated to 1000 (dbar) with an initial accuracy of ±0.05% full scale and a resolution <0.001% full scale so 1 cm. Sampling was at 1 minute intervals and sensor response time is <0.01s. The three instruments were at pressures of 425, 495 and 648 dbar respectively and all three gave ...